1996
DOI: 10.1093/nar/24.24.4910
|View full text |Cite
|
Sign up to set email alerts
|

Protonatable Hairpins Are Conserved in the 5'-Untranslated Region of Tymovirus RNAs

Abstract: The secondary structures of the 5'-untranslated region (5'-UTR) of five different tymoviruses have been determined by structure probing, computer prediction and sequence comparison. Despite large sequence differences, there are remarkable similarities in the secondary structure. In all viruses two or four hairpins are found, most of which contain a symmetrical internal loop consisting of adjacent C-C or C-A mismatches. Since it is known that such mismatches can be protonated and protonated cytosines play an im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0
4

Year Published

1999
1999
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 48 publications
4
31
0
4
Order By: Relevance
“…The 5'-UTR of all the previously described species can be folded in a series of hairpins, three in most species, with protonable internal loops consisting in C-C and C-U mismatches [29,44]. Important functional roles in encapsidation, translation and viral accumulation have been assigned to these hairpins [45].…”
Section: Discussionmentioning
confidence: 99%
“…The 5'-UTR of all the previously described species can be folded in a series of hairpins, three in most species, with protonable internal loops consisting in C-C and C-U mismatches [29,44]. Important functional roles in encapsidation, translation and viral accumulation have been assigned to these hairpins [45].…”
Section: Discussionmentioning
confidence: 99%
“…5'-UTR of TYMV gRNA has two hairpin structures, which had been implicated both in replication and encapsidation of viral RNA. Two hairpins present in TYMV 5'-UTR contain a symmetrical internal loop consisting of C-C or C-A mismatches (9).…”
Section: Turnip Yellow Mosaic Virus (Tymv) Is a Positive-strandmentioning
confidence: 99%
“…Despite large sequence differences, Hellendoorn et al (4) observed remarkable similarity among tymoviruses in the secondary structures of their 5' untranslated regions (5'-UTR), which contain a symmetrical internal loop consisting of C-C or C-A mismatches. Hairpin structures containing the mismatches were reported to become more stable at low pH by C-C and C-A base pairing due to protonated C residues (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Hairpin structures containing the mismatches were reported to become more stable at low pH by C-C and C-A base pairing due to protonated C residues (4,5). TYMV gRNA has two such hairpin structures in its 5'-UTR, which were reported to be essential for replication and long-distance systemic movement; lack of the 5'-UTR hairpins resulted in significantly reduced disease symptoms and deficient viral spread (6).…”
Section: Introductionmentioning
confidence: 99%